Equilibrium magnesium isotope fractionation between aqueous Mg2+ and carbonate minerals: Insights from path integral molecular dynamics. (15th August 2015) - Pinilla, Carlos; Blanchard, Marc; Balan, Etienne; Natarajan, Suresh K.; Vuilleumier, Rodolphe; Mauri, Francesco
Abstract: The theoretical determination of the isotopic fractionation between an aqueous solution and a mineral is of utmost importance in Earth sciences. While for crystals, it is well established that equilibrium isotopic fractionation factors can be calculated using a statistical thermodynamic approach based on the vibrational properties, several theoretical methods are currently used to model ions in aqueous solution. In this work, we present a systematic study to determine the reduced partition function ratio ( β -factor) of aqueous Mg 2+ using several levels of theory within the simulations. In particular, using an empirical force field, we compare and discuss the performance of the exact results obtained from path integral molecular dynamics (PIMD) simulations, with respect to the more traditional methods based on vibrational properties and the cluster approximation. The results show the importance of including configurational disorder for the estimation of the equilibrium isotope fractionation factor. We also show that using the vibrational frequencies computed from snapshots taken from equilibrated classical molecular dynamics represents a good approximation for the study of aqueous ions. Based on these conclusions, the β -factor of aqueous Mg 2+ have been estimated from a Car–Parrinello molecular dynamics (CPMD) simulation with an ab initio force field, and combined with the β -factors of carbonate minerals (magnesite, dolomite, calcite and aragonite). Mg β -factor of Mg-bearing aragonite, calculated here for the first time, displays a lower value than the three other carbonate minerals. This is explained by a strong distortion of the cationic site leading to a decrease of the coordination number during Ca–Mg substitution. Overall, the equilibrium magnesium isotope fractionation factors between aqueous Mg 2+ and carbonate minerals that derive from this methodological study support the previous theoretical results obtained from embedded cluster models.